Study on Water Transport Mechanisms of the PEMFC Based on a Visualization Platform and Water Balance Model - Xin Zhao (Hindawi Limited, 2021)
It is widely acknowledged that the water balance issue is extremely important for improving the performance and durability of the proton exchange membrane fuel cell. In the presented paper, the visualization platform of the single fuel cell and the water balance model were built to investigate the water transport mechanisms. A transparent 25 cm2 single fuel cell with serpentine flow channels was adopted. Based on the experimental data, firstly, the change rate of water content in the fuel cell was calculated quantitatively and the reliability of the water balance model was rigorously validated. Then, the water state in the fuel cell as the qualitative finding was observed online to assist the research of water transport mechanisms. Finally, the effects of inlet gas temperature, inlet gas humidity, and hydrogen/air stoichiometry on the EIS, the voltage, and the water content in the fuel cell were studied quantitatively, respectively. The corresponding relationship between the performance and the water content in the fuel cell was obtained.